2017
DOI: 10.17957/tpmj/17.3708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression; A Cross-Sectional Study Among MBBS Students of Sargodha Medical College, Sargodha Pakistan

Abstract: Material and Methods: A sample of 200 medical students (including 147 female and 53 male) was chosen by random sampling. PHQ-9 scale was used to evaluate depression among participants. Data was collected on a specially designed questionnaire containing sociodemographic and educational characteristics and was analyzed using SPSS 16.0. Results: Out of 200 respondents, who participated in study, 75.5% reached depression criteria. The age range of majority of students (53%) was 20-22 year. Factors such as female g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
3
1
0
Order By: Relevance
“…Interestingly, depression was significantly higher among students in the lower age group and those studying in their 1st year of MBBS. This is consistent with a study conducted in Pakistan reporting higher rates of depression among students in earlier phases of their medical careers (Uttra et al 2017). Moreover, Puthran et al (2016 have found a reduced tendency of depression in later years of the medical course.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, depression was significantly higher among students in the lower age group and those studying in their 1st year of MBBS. This is consistent with a study conducted in Pakistan reporting higher rates of depression among students in earlier phases of their medical careers (Uttra et al 2017). Moreover, Puthran et al (2016 have found a reduced tendency of depression in later years of the medical course.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, depression was significantly higher among students in the lower age group and those studying in the first year of MBBS. This is in consistent with a study conducted in Pakistan reporting higher rates of depression among students in earlier phases of medical carrier (Uttra et al 2017). Moreover, Puthran et al have found a reduced tendency of depression in later years of the medical course (Puthran et al 2016).…”
Section: Association Of Mental Health Status With Demographic Variablessupporting
confidence: 91%
“…Other studies also show similar findings regarding the academic year of medical students and their mental health [13,18,19]. Interestingly, the during COVID-19 pandemic, doing physical exercise was linked to decreased depression and anxiety.…”
Section: Discussionsupporting
confidence: 60%